Effect of Sulfate on Carbon Monoxide Conversion by a Thermophilic Syngas-Fermenting Culture Dominated by a Desulfofundulus Species - Alves, Joana I.; Visser, Michael; Arantes, Ana L.; Nijsse, Bart; Plugge, Caroline M.; Alves, M. Madalena; Stams, Alfons J. M.; Sousa, Diana Z. (Frontiers in Microbiology, 2020)
A syngas-degrading enrichment culture, culture T-Syn, was dominated by a bacterium closely related to Desulfofundulus australicus strain AB33T (98 % 16S rRNA gene sequence identity). Culture T-Syn could convert high CO concentrations (from pCO ≈ 34 kPa to pCO ≈ 170 kPa), both in the absence and presence of sulfate as external electron acceptor. The products formed from CO conversion were H2 and acetate. With sulfate, a lower H2/acetate ratio was observed in the products profile, but CO conversion rates were similar to those in the absence of sulfate. The ability of D. australicus strain AB33T to use CO was also investigated. D. australicus strain AB33T uses up to 40 % CO (pCO ≈ 68 kPa) with sulfate and up to 20 % CO (pCO ≈ 34 kPa) without sulfate. Comparison of the metagenome-assembled genome (MAG) of the Desulfofundulus sp. from T-Syn culture with the genome of D. australicus strain AB33T revealed high similarity, with an ANI value of 99 % and only 32 unique genes in the genome of the Desulfofundulus sp. T-Syn. So far, only Desulfotomaculum nigrificans strain CO-1-SRB had been described to grow with CO with and without sulfate. This work further shows the carboxydotrophic potential of Desulfofundulus genus for CO conversion, both in sulfate-rich and low-sulfate environments.